Current knowledge of medical complications in adults with achondroplasia: A scoping review. Issue 1 (22nd April 2019) - Fredwall, Svein O.; Maanum, Grethe; Johansen, Heidi; Snekkevik, Hildegun; Savarirayan, Ravi; Lidal, Ingeborg B.
Abstract : This article provides an overview of the current knowledge on medical complications, health characteristics, and psychosocial issues in adults with achondroplasia. We have used a scoping review methodology particularly recommended for mapping and summarizing existing research evidence, and to identify knowledge gaps. The review process was conducted in accordance with the PRISMA‐ScR guidelines (Preferred Reporting Items for Systematic reviews and Meta‐Analyses Extension for Scoping Reviews). The selection of studies was based on criteria predefined in a review protocol. Twenty‐nine publications were included; 2 reviews, and 27 primary studies. Key information such as reference details, study characteristics, topics of interest, main findings and the study author's conclusion are presented in text and tables. Over the past decades, there has only been a slight increase in publications on adults with achondroplasia. The reported morbidity rates and prevalence of medical complications are often based on a few studies where the methodology and representativeness can be questioned. Studies on sleep‐related disorders and pregnancy‐related complications were lacking. Multicenter natural history studies have recently been initiated. Future studies should report in accordance to methodological reference standards, to strengthen the reliability and generalizability of the findings, and to increase the relevance for implementing in clinical practice. Abstract :